Enhancement of the IEEE 802.11 Power Saving Mode by Prioritized Reservations - Xiaoying Lei; Seung Hyong Rhee (International Journal of Distributed Sensor Networks)
The increasing demand for real-time applications in WSN has raised the requirement of protocols considering both energy efficiency and end-to-end delay. A PSM is proposed in the IEEE 802.11 protocol to reduce the power consumptions of wireless nodes. Wireless nodes can stay in doze mode and periodically wake up to retrieve the frames buffered in the APs. However, the 802.11 PSM is not such energy efficiency for WSN. First, in the process of the node's transmitting polling frames to AP, channel contentions may cause sensor nodes to deplete power quickly. Second, the mechanism of retrieving buffered frames can be inefficient since a polling frame is able to pick up only one data frame. Third, a prioritized service for urgent needs is not supported. In this paper, we propose a prioritized reservation scheme to enhance the IEEE 802.11 PSM. The concept of PSCW is suggested, during which PSM sensor nodes can retrieve the buffered frames using the reserved SPs, where the priorities of the PSM nodes are considered in scheduling the SPs. Through analytic models and discrete simulations, we show that our proposed mechanism outperforms the existing PSM schemes in terms of energy efficiency and prioritized services.